Tindakan Kekerasan Terhadap Pekerja Migran Indonesia Perempuan: Faktor Penyebab, Bentuk Kekerasan, Dan Strategi Penanggulangannya - Nursani, Adila; Suherman, Anisa Salsabila; Apriliani, Berliana Mawar; Sofyan, Keysa Kailani; Nadiawati, Khansa; Hermawanti, Kori; Utami, Tanti Kirana (Majelis: Jurnal Hukum Indonesia, 2026)
Abstract. This study aims to examine the causes, forms, and strategies for combating violence against female Indonesian migrant workers (PMI) from a legal, sociological, and gender perspective. The background of this research is based on the vulnerability of female PMI to various forms of physical, psychological, sexual, and economic violence, which occurs from the pre-placement stage to the post-placement stage, as well as the long-term impact on mental health, human rights, and socio-economic reintegration. The method used is empirical legal with primary data collection through in-depth interviews with female PMI victims of violence and accompanying institutions, as well as secondary data in the form of literature reviews, laws and regulations, and scientific publications. The analysis was conducted using descriptive qualitative methods, integrating human rights theory, Feminist Legal Theory, and international migration policy. The results of the study show that the vulnerability of female migrant workers is caused by economic factors, education, patriarchal culture, non-transparent recruitment processes, the characteristics of work in the informal sector, power imbalances with employers, and weak legal protection in the destination country. The forms of violence experienced include beatings, sexual harassment, threats, social isolation, wage withholding, and structural exploitation practices. Protection efforts implemented include preventive approaches through training, legal education, legal document guarantees, and assistance from law enforcement agencies, as well as repressive approaches through action against perpetrators of violence and bilateral cooperation with destination countries. This study emphasizes the importance of comprehensive and sustainable protection for female Indonesian migrant workers, covering all stages of labor migration as well as strengthening digital-based monitoring systems, officer capacity, and cross-sector collaboration to ensure the safety, dignity, and fulfillment of the human rights of female Indonesian migrant workers.